SOSIALISASI SISTEM PELAYANAN PUBLIK BERBASIS ONLINE DI KANTOR KECAMATAN PADANGSIDIMPUAN BATUNADUA - Indra Syahputra Marpaung; Tri Eva Juniasih; Nurbaya Harianja; Wawan Patriansyah; Rina Tiur Lona; Emirza Henderland Harahap (COVIT (Community Service of Health), 2023)
The development of information and communication technology is currently very rapid. Everyone is required to be able to use it in fulfilling the ease of obtaining the expected needs. The Padangsidimpuan Batunadua sub-district office is no exception, where the office has the main task of serving the community and fulfilling administrative needs as an Indonesian citizen. In serving, it takes understanding in the field of service systems and how to improve the quality of these services. One of the activities that can be carried out to increase the understanding of sub-district office employees about public services is socialization. The benefit of this socialization is to improve the quality of service and fulfill community satisfaction. From the results of this socialization activity, the participants increasingly understood the online-based public service system, knew the steps for making a web, and how to utilize the internet network, the right communication network. This activity received a very good response from the participants, was active in asking questions, and hoped that there would be other activities that would support their work at the Padangsidimpuan Batunadua sub-district office. Keywords: Outreach, Public Service, Online